The Relationship between Burnout and Emotional Labor among Social Service Workers: The Case of Adiyaman - Karakaplan Özer, Emine; Doğan, Edip (My University, 2022)
Emotional labor, which can be defined as a set of regulatory behaviors performed by employees at workplace, and burnout, which is defined as a state of exhaustion, cynicism, and a reduction in professional productivity, are two important subjects in organizational behavior literature. It is, therefore, important to carry out empirical studies about these subjects. The aim of this study is to reveal the relationship between the three sub-dimensions of emotional labor and the three sub-dimensions of burnout. Ethical permission for this study was obtained from Adıyaman University Social and Human Sciences Ethics Committee with the date 28.01.2021 and number 51. In this context, employees from the Family, Labor, and Social Services Directorates in Adyaman and other regions have been asked to fill out a questionnaire.The data obtained from the research have been transferred to the SPSS 25 program and analyzed. As a result of the research, it has been seen that surface acting has in a positive and significant relationship with emotional exhaustion and depersonalization. In addition, it has been determined that deep acting has a positive and significant relationship with depersonalization and personal achievement. Finally, while natural behavior has a negative and significant relationship with emotional exhaustion and depersonalization, it has been found to have a positive and significant relationship with personal achievement.